The Advantage of High Throughput Sequencing for the Diagnosis of Child Shwachman-Diamond Syndrome - Li, Na; Zhang, Li; Yu, Xin Bo; Zhu, Jing; Liu, Zheng Juan (Archives of Clinical and Medical Case Reports, 2019)
Background: Shwachman-Diamond syndrome is a rare autosomal recessive disorder with an incidence of 1/76000. It is caused by biallelic pathogenic variants in SBDS allele, characterized by pancreatic exocrine insufficiency, abnormal blood system, and skeletal abnormalities. Here, we describe the diagnosis of a child with Shwachman-Diamond syndrome and discuss the main clinical symptoms of Shwachman-Diamond syndrome and the importance of genetic testing for its diagnosis. Case description: A 5.5 year-old boy was hospitalized in our ward of the Second Affiliated Hospital of Dalian Medical University due to short stature. The patient was also found to have significantly reduced or lack of neutrophils, repeated infections, and thrombocytopenia. Clinical symptoms suggested the patient suffered from Shwachman-Diamond syndrome. This was confirmed two years later by gene sequencing: compound heterozygous pathogenic variants exon2 deletion and c.258+2T>C in SBDS gene were detected. They were verified by qPCR or Sanger sequencing. Conclusion: Shwachman-Diamond Syndrome may have pathological changes in multiple systems and is characterized by pancreatic exocrine dysfunction and abnormal blood cells. The clinical symptoms include growth retardation, intermittent or persistent cytopenia, repeated infections due to neutropenia. Shwachman-Diamond Syndrome is a genetic disease and gene sequencing is helpful to confirm the diagnosis.